Advanced planning and scheduling system with application in the tobacco industry. (2017) - Zhang, Haijun; Yan, Qiong; Peng, Xiying
For the reasonable and real-time planning, this paper proposes a case study of an advanced planning and scheduling system called APSoCT, which is developed for the tobacco industry. Firstly, the cut tobacco processing is modelled. Then, the function modules, the planning process and the intelligent heuristic are designed for APSoCT. The optimisation objectives included the changeover, the shift balance, the facility utilisation, the continuous-batch production and so on. Finally, APSoCT is developed to verify the system design is feasible and reliable. The APSoCT system fulfils the requirements of cut tobacco flow shop in the tobacco industry.